Odpowiedzi

2010-01-21T15:10:08+01:00
-5+(-9)=-5-9=-14
-9-(-5)=-9+5=-4
-5x-9=-5x-9
(-5)x-9=-5x-9
-5-(-9)=-5+9=4
-5+(-9)=-5-9=-14
-5/(-9)=5/9
(-9)/(-5)=9/5


(-2+5)x(-3)=3-3x
(4-(-6)/(-2))=4-3=1
(-13-8)/(-3+10)=-21/7=-3
2010-01-21T16:00:06+01:00
1.Oblicz :
-5+-9=-5-9=-14
-9-(-5)=-9+5=-4
-5x-9=45
(-5)x-9=-5x-9=45
-5-(-9)=-5+9=4
-5+(-9)=-5-9=-14
-5:(-9)=-5x(-1/9)=5/9
(-9):(-5)=-9x(-1/5)=9/5

2.Oblicz:
a)(-2+5)x(-3)=(3)x(-3)=-9
b)(4-(-6):(-2)=(4+6):(-2)=10:(-2)=10x(-1/2)=-10/2=-5
c)(-13-8):(-3+10)=(-21):(7)=-21x1/7=-21/7=-3